Medication adherence among Japanese patients with developmental disabilities: a survey study - Ando, Mutsumi; Taki, Iori; Yamazaki, Taigi; Hida, Noriko (Frontiers in Psychiatry, 2024)
Aim Developmental disabilities (DD) often persist into adulthood, necessitating early and continuous treatment. Although pharmacotherapy is a viable treatment option, managing medication can be challenging. Prior research has not explored medication use among patients with DD in Japan. Thus, this study aimed to identify the medication challenges faced by these patients. Methods A questionnaire survey was administered to 200 outpatients to collect data on the number of prescribed medications, the timing of administration, the frequency of missed doses, and the use of medication notebooks. This was a prospective observational study without intervention and a random sampling. Results The survey revealed that 57.0% of the participants were non-adherent to their medication regimen. Specifically, medication non-adherence rates were 44.7% among individuals with autism spectrum disorder (ASD), 86.9% for those with attention deficit hyperactivity disorder (ADHD), and 30.4% for patients with comorbid ASD and ADHD. Despite 48.3% of the participants taking measures to prevent forgetting their medication, 65.3% of them still failed to take their medication as prescribed. The possession rate of medication record books was 96.0%. Conclusion The study indicates that the frequency of medication non-adherence among patients with DD in Japan mirrors that in other countries. Patients who reported taking preventative measures still experienced high rates of non-adherence, suggesting limited effectiveness of these strategies. It is essential to develop more effective measures to improve adherence, enhance disease awareness, and increase understanding of medication instructions. The high possession rate of medication record books suggests they could play a significant role in managing DD, and their use is expected to increase in the future.